Overview of Media Poster Effectiveness about Tuberculosis to Knowledge, Attitudes, and Behavior of Puskesmas Visitors Leuwiliang Kabupaten Bogor - Fahmi Firdaus; Asri Masitha Arsyati; Supriyanto Supriyanto (PROMOTOR, 2023)
Posters are one of the visual media that can play an important role in preventing littering behavior. By the definition of posters which are media used to convey certain information, suggestions, or ideas, to stimulate the desire of those who see them to carry out the content. This study used a quantitative approach. This research is research with Cross-sectional method. This method is considered by the purpose of this study, namely Knowing the picture of the effectiveness of poster media on increasing knowledge and attitudes of visitors to the Leuwiliang Health Center. The results of the study described the knowledge variables of bad respondents as many as 44 people (54.3%) and the category of good respondent knowledge variables as many as 37 people (45.7%), the behavioral variables of respondents did not do as many as 41 people (50.6%) and the category of behavioral variables of respondents did as many as 40 people (49.4%), negative respondent attitude variables as many as 1 person (1.2%) and the variable category of positive respondent attitudes as many as 80 people (98.8%), The respondents' media type variable did not understand as many as 21 people (60%) and the respondent's media type variable category understood as many as 60 people (74.1%).